The Role of Tahfidzul Quran Learning to Build the Students’ Character at Madrasah Ibtidaiyah Istiqomah Sambas Purbalingga - Arifin, Ikhwandi (International Conference of Moslem Society, 2018)
This paper discusses the importance of the students ‘character building in the level of primary school/Islamic elementary school to face the globalization and information era. Education is the process of determining the nation’s character. Good or bad character of the nation in the future will be determined by the present quality of education. Building the character through Tahfidzul Quran learning approach is expected to be the main foundation to improve the degree and prestige of learners as the asset of the nation. This study aimed to describe the process of Tahfidzul Quran learning which included planning, organizing, doing action and monitoring the important role of learning itself to build the learners’ character, especially in Madrasah Ibtidaiyah Istiqomah Sambas Purbalingga.